Rôle et limites des tiers-lieux dans la fabrique des villes contemporaines - Raphaël Besson (Université Lille 1, 2017)
The notion of ‘third place’ is usually applied in an empirical way. It covers multiple realities, such as projects of co-working spaces, living labs and fab labs. Some third places are especially concerned with the city and the new conditions of urban fabrication. Relying on open innovation methods and on digital potential, these Third Places defend the idea of an urbanism which is not only the domain of experts, but would also be co-produced with a city’s inhabitants. They defend a right to infrastructure in cities (whether material or immaterial). To question the role and scope of Third Places in the fabrication of contemporary cities, we will focus on the analysis of French and Spanish Third Places specialising in urbanism. This analysis leads to a better understanding of the role of Third Places in urban production, and will highlight the difficulties of the construction of an urban policy of Third Places.